Togo – 2011: Domestic politics, foreign affairs, and socio-economic development - Dirk Kohnert (Africa Yearbook Volume 8: Politics, Economy and Society South of the Sahara in 2011, 2012)
The coalition government continued on the path to establishing democracy, good governance and the rule of law in Togo in 2011. Its efforts were honoured by the international donor community with growing commitments and the cancellation of foreign debt. Domestic politics were dominated by simmering confrontations within both the opposition and the ruling Gnassingbé clan. The president successfully followed the divide-and-rule strategy of his late father, Eyadéma. The radical opposition remained isolated and its MPs excluded from parliament, despite a ruling of the ECOWAS Court of Justice to the contrary. The showdown between the president and his rivals within the Gnassingbé clan culminated in the conviction of Kpatcha Gnassingbé and his followers as ringleaders of the 2009 coup attempt. – – Die Koalitionsregierung setzte 2011 ihren Weg zum Aufbau von Demokratie, guter Regierungsführung und Rechtsstaatlichkeit in Togo fort. Ihre Bemühungen wurden von der internationalen Gebergemeinschaft mit wachsenden Zusagen und dem Erlass von Auslandsschulden honoriert. Die Innenpolitik wurde von schwelenden Auseinandersetzungen innerhalb der Opposition und des herrschenden Gnassingbé-Clans dominiert. Der Präsident setzte erfolgreich die Strategie des Teilens und Herrschens seines verstorbenen Vaters Eyadéma um. Die radikale Opposition blieb isoliert und ihre Abgeordneten wurden vom Parlament ausgeschlossen, obwohl der ECOWAS-Gerichtshofs dies verurteilte. Der Showdown zwischen dem Präsidenten und seinen Rivalen innerhalb des Gnassingbé-Clans gipfelte in der Verurteilung von Kpatcha Gnassingbé und seinen Anhängern als Anführer des Putschversuchs von 2009.
Additional information: Author's version
Keywords: F35; F54; N47; Z13; 330; Togo; Africa Yearbook 2011; domestic policy; foreign affairs; socio-economic development; period under review 2011